A review on ecology, biology, and management of a detrimental pest, Tuta absoluta (Lepidoptera: Gelechiidae) - Shubh Pravat Singh Yadav; Sukritee Bhattarai; Netra Prasad Ghimire; Bishnu Yadav (Future Science, 2022)
Insect pests are the forcing barrier for crop production worldwide. Of those insects, lepidopteran forms a major group of pests damaging from larval, pupal to adult stages. A leaf-mining insect i.e., Tuta absoluta of the lepidopteran group is a serious pest of tomato throughout the globe. The widespread outreach resulting from this challenging pest posed a great threat in every habituated continent recently. The extensive infestations fortified by feeding grubs on tomato and other Solanaceous crops have unprecedented economic losses of the yield. Due to the entophytic nature of the pest, it makes growers difficult to manage the tomato leaf miner pest. So, every approach is to be foreseen to manipulate the pest environment not favoring them for survival, multiplication, and growth. Thence, a complete package of useful tactics including physical, biological, mechanical, biotechnical, botanical, and chemical measures are fruitful to harness the real impact of pest management. The best control strategies are accessed and complied herein considering the actual know-how on the nature of pests and effective mitigating measures to assure the crops in this review paper.